Polyaniline All Solid-State Pseudocapacitor: Role of Morphological Variations in Performance Evolution. (1st April 2016) - Grover, Sonia; Goel, Shubhra; Marichi, Ram Bhagat; Sahu, Vikrant; Singh, Gurmeet; Sharma, Raj Kishore
Graphical abstract: Abstract: We report a facile soft-template approach to develop polyaniline (PANI) nanostructures in various morphologies (nanotube, nanorod, nanosphere and nanosheet) by triggering the amount of N-cetyl-N, N, N-trimethyl trimethylammonium bromide (CTAB) surfactant. The possible mechanistic pathways for the formation of PANI structures explain the occurrence of different growth patterns and the aggregation archetype of monomeric units in undertaken polymerization reaction. Brunauer-Emmett-Teller measurements reveal that PANI nanotube possess highest surface area (33.8 m 2  g −1 ) due to availability of hollow central portion, while the 1D ordered arrangement of aniline units significantly increase its conductivity (0.92 mS cm −1 ). Pseudocapacitive performance of these morphologically different PANI electrodes in all solid-state supercapacitor cells is studied using a solid electrolyte (PVA/H2 SO4 ). Electrochemical attributes of solid-state pseudocapacitor cells clearly indicate that nanotube exhibits highest specific capacitance (367 F g −1  at 5 mV s −1 ) among all PANI forms, and can be cycled successfully up to continuous 1000 GCD cycles retaining more than 91.5% capacitance in PVA/H2 SO4 electrolyte at high current density of 5 A g −1 .